Exploring the complex realities of nursing work in Kenya and how this shapes role enactment and practice—a qualitative study - Mbuthia, D; Brownie, S; Jackson, D; McGivern, G; English, M; Gathara, D; Nzinga, J (Wiley, 2023)
Aim: We explore how nurses navigate competing work demands in resource-constrained settings and how this shapes the enactment of nursing roles. Design: An exploratory-descriptive qualitative study. Methods: Using individual in-depth interviews and small group interviews, we interviewed 47 purposively selected nurses and nurse managers. We also conducted 57 hours of non-participant structured observations of nursing work in three public hospitals. Results: Three major themes arose: (i) Rationalization of prioritization decisions, where nurses described prioritizing technical nursing tasks over routine bedside care, coming up with their own ‘working standards’ of care and nurses informally delegating tasks to cope with work demands. (ii) Bundling of tasks describes how nurses were sometimes engaged in tasks seen to be out of their scope of work or sometimes being used to fill for other professional shortages. (iii) Pursuit of professional ideals describes how the reality of how nursing was practised was seen to be in contrast with nurses' quest for professionalism.